New insights into the analysis of the electrode kinetics of flavin adenine dinucleotide redox center of glucose oxidase immobilized on carbon electrodes - Simonov, Alexandr N (Langmuir : the ACS journal of surfaces and colloids, 2014)
New insights into electrochemical kinetics of the flavin adenine dinucleotide (FAD) redox center of glucose-oxidase (GlcOx) immobilized on reduced graphene oxide (rGO), single- and multiwalled carbon nanotubes (SW and MWCNT), and combinations of rGO and CNTs have been gained by application of Fourier transformed AC voltammetry (FTACV) and simulations based on a range of models. A satisfactory level of agreement between experiment and theory, and hence establishment of the best model to describe the redox chemistry of FAD, was achieved with the aid of automated e-science tools. Although still not perfect, use of Marcus theory with a very low reorganization energy (≤0.3 eV) best mimics the experimental FTACV data, which suggests that the process is gated as also deduced from analysis of FTACV data obtained at different frequencies. Failure of the simplest models to fully describe the electrode kinetics of the redox center of GlcOx, including those based on the widely employed Laviron theory is demonstrated, as is substantial kinetic heterogeneity of FAD species. Use of a SWCNT support amplifies the kinetic heterogeneity, while a combination of rGO and MWCNT provides a more favorable environment for fast communication between FAD and the electrode